Morphological character and simplicia of galangal (alpina galanga L.) in Bangkalan - Moh. Rizal; Mustika Tripatmasari; Diana Nurus Sholehah (Agrovigor, 2025)
The aim of this research is to determine the differences in morphology, growth and yield of simplicia galangal in several sub-districts in Bangkalan. This research uses a purposive sampling method where the determination of sample locations is carried out based on the snowball sampling. The results of this research show that the morphological characters of galangal in Socah, Geger and Kamal have no differences in characteristics of the leaf color, leaf shape, leaf tip, leaf base, leaf surface, stem type, stem color, stem shape, stem surface, root type, root shape, root color, rhizome skin color and rhizome flesh color. The results of the Independent T Test with a level of 95% on the growth and production parameters of galangal show that there are differences in root length in Socah and Geger for the number of leaves, number of roots and root length in Kamal and Socah. Meanwhile, in Geger and Kamal, there are differences in the number of leaves, plant height and number of roots. The yield of the rhizome simplicia of the galangal shows that there are differences between Geger and Kamal District.